EU AGENCIFICATION AND THE RISE OF ESMA: ARE ITS GOVERNANCE ARRANGEMENTS FIT FOR PURPOSE?. (July 2019) - Howell, Elizabeth
Abstract: EU agencies have mushroomed in recent years and new agencies, such as those in the financial arena, can have far-reaching quasi-regulatory and supervisory powers. These developments raise fundamental questions as to their constitutional standing, the delegation of powers and how to wrestle the challenges of independence and accountability. This paper considers ESMA, the most ambitious new financial sector agency. It examines ESMA's governance and accountability mechanisms and makes normative proposals to better balance the competing supranational and national interests within it. Such refinements should also be implemented in conjunction with additional accountability requirements, particularly a greater role for the European Parliament. This reshaping is vital to guarantee ESMA's autonomy and legitimacy.